fizika o‘qitishda talabalarning ijodiy qobiliyatlarini rivojlantirish - Matjanov, N.S. (SCIENCE and SOCIETY, 2023)
The article describes the peculiarity of the development of students’ creative abilities in the process of teaching physics. Information is also given about interactive methods (case studies, problem-based learning) that ensure the development of students’ creative abilities.